Do intravitreal anti-vascular endothelial growth factor agents lead to renal adverse events? A pharmacovigilance real-world study - Jiang, Lin; Peng, Liying; Zhou, Yangzhong; Chen, Gang; Zhao, Bin; Li, Mingxi; Li, Xuemei (Frontiers in Medicine, 2023)
Purpose Intravitreal vascular endothelial growth factor (VEGF) blockade is essential in many macular edema diseases treatment. However, intravitreal VEGF treatment has been reported to lead to deteriorated proteinuria and renal function. This study aimed to explore the relationship between renal adverse events (AEs) and the intravitreal use of VEGF inhibitors. Method In the FDA’s Adverse Event Reporting System (FAERS) database, we searched for renal AEs of patients receiving various anti-VEGF drugs. We performed statistics on renal AEs in patients treated with Aflibercept, Bevacizumab, Ranibizumab, and Brolucizumab (from January 2004 to September 2022) using disproportionate and Bayesian analysis. We also investigated the time to onset, fatality, and hospitalization rates of renal AEs. Results We identified 80 reports. Renal AEs were most frequently associated with Ranibizumab (46.25%) and Aflibercept (42.50%). However, the association between intravitreal anti-VEGFs and renal AEs was insignificant since the reporting odds ratio of Aflibercept, Bevacizumab, Ranibizumab, and Brolucizumab were 0.23 (0.16, 0.32), 0.24 (0.11, 0.49), 0.37 (0.27, 0.51) and 0.15 (0.04, 0.61), respectively. The median time to renal AEs onsets was 37.5 (interquartile range 11.0–107.3) days. The hospitalization and fatality rates in patients who developed renal AEs were 40.24 and 9.76%, respectively. Conclusion There are no clear signals for the risk of renal AEs following various intravitreal anti-VEGF drugs based on FARES data.